Primary thyroid tuberculosis associated with thyrotoxicosis - Rare presentation - -, Manju; Krishna, Mani; Singh, Gopal (Indian Journal of Case Reports, 2020)
Primary thyroid tuberculosis (TB) gland is a very rare disease; although, the incidence of extra pulmonary TB has been increasing in the recent year. We present a case of primary thyroid TB. The case was diagnosed on the basis of findings of fine-needle aspiration cytology, as our case presented with multinodular thyroid goitre and erythema nodosum. She was given antitubercular treatment for 9 months, and she improved and her multinodular lesion completely resolved after treatment. In conclusion, thyroid TB should be kept in mind in the differential diagnoses of the thyroid masses, even in a patient with no history and symptoms of TB disease.